Challenges and Problems of Rural Entrepreneurship: An Explorative Study of Government’s Role in Entrepreneurship - Kaur, Sukhmeet (AMC Indian Journal of Entrepreneurship, 2019)
’Come to India’ and ’Invest in India’ were calls given by India’s Prime Minister Mr. Narendra Modi at the World Economic Forum 2018 at Davos to foreign investors. He claimed that India would be reaching 5 Trillion dollar economy by 2025. The World Economic Forum (WEF) stated that Global Competitive Index of India has moved to 58th position out of 140 economies, which is the highest gain for any G20 country. India holds 23rd rank in degree of entrepreneurship. The Make in India campaign, Digital India, influx of AI, and IoT in organizations to make decisions, taxpayer-friendly laws like Goods and Services Tax (GST) amendment bill, banking sector reforms, bankruptcy code for bad debtors, urea, and ethanol as a source of producing electricity, coal auctions, and Start-up India scheme are some initiatives taken by the Indian government to promote both employability and entrepreneurship. Adjunct platforms like Skill India and Stand-up India, Skill development mission, and financial loans through MUDRA (Micro Units Development and Refinance Agency Limited) Bank are designed to support integral entrepreneurial spirit among young entrepreneurs. Besides all these colossal schemes, few factors should be re-considered for upward mobility of entrepreneurs who wanted to turn their dream into reality in rural areas. Factors like lack of entrepreneurial skills and competencies, dearth of funds, lack of infrastructure like water, electricity, transportation etc. The paper attempted to identify major challenges and problems confronted by entrepreneurs in terms of utilizing their own resources and initiatives or schemes provided by the Indian government in rural areas. The present study also analyzed the contribution made by rural entrepreneurs in economic development. In order to reach the objectives, an explorative study was conducted. The conclusion and the way forward are also discussed.